Navigating operational excellence: A strategic framework for enhancing sustainable logistics performance at Indonesian International Airport - Syafrianita Syafrianita; Agus Purnomo; Adang Haryaman; Kiagus Muhammad Amran; Hariyanto Hariyanto; Cahyat Rohyana (Decision Science Letters)
Research on measuring airport operational performance has predominantly focused on technical aspects. However, there is still a need for studies to be conducted on measuring sustainable logistics and operational performance at international airports. The objective of this study is to develop a comprehensive measurement system for the Airport Operations Division in Indonesia that incorporates both operational and sustainable logistics performance. This will be achieved by integrating the company's vision, mission, and strategy into various performance measures using the Balanced Scorecard concept. The research methodology employed quantitative research methods, including primary data collection through observation and questionnaires. These questionnaires were developed using a pairwise comparison matrix derived from the Analytical Hierarchy Process (AHP). Data was collected from five international airports in Indonesia. The findings of the study demonstrate that the application of the Balanced Scorecard, coupled with the Objective Matrix method for setting performance targets and enriched with the AHP approach, enables the identification of priorities and assessment of performance. The research emphasizes the significance of considering non-financial aspects when measuring airport performance. This is crucial for supporting strategic decision-making and promoting sustainable performance improvement.